ChemInform Abstract: A Polyoxometalate‐Based Single‐Molecule Magnet with a Mixed‐Valent MnIV2MnIII6Mn II4 Core. Issue 22 (13th May 2013) - Zhang, Zhi‐Ming; Yao, Shuang; Li, Yang‐Guang; Wu, Hai‐Hong; Wang, Yong‐Hui; Rouzieres, Mathieu; Clerac, Rodolphe; Su, Zhong‐Min; Wang, En‐Bo
Abstract K8Na10{ [MnIV2MnIII6Mn II4(μ3‐O)6 (μ‐OH)4(H2O)2 (CO3)6] [B‐β‐SiW6O26] 2}·30H2O is synthesized from an aqueous mixture of K8[β2‐SiW11O39], MnCl2, NaCl, 2, 3‐pyrazinedicarboxylic acid, and K2CO3 (pH 10.2, 50 °C, 5 h, 38% yield).